Comparison of the Prognostic Significance of Initial Blood Lactate and Base Deficit in Trauma Patients. (March 2017) - Raux, Mathieu; Le Manach, Yannick; Gauss, Tobias; Baumgarten, Romain; Hamada, Sophie; Harrois, Anatole; Riou, Bruno; Duranteau, Jacques; Langeron, Olivier; Mantz, Jean; Paugam-Burtz, Catherine; Vigue, Bernard
Abstract : Background: Initial blood lactate and base deficit have been shown to be prognostic biomarkers in trauma, but their respective performances have not been compared. Methods: Blood lactate levels and base deficit were measured at admission in trauma patients in three level 1 trauma centers. This was a retrospective analysis of prospectively acquired data. The association of initial blood lactate and base deficit with mortality was tested using receiver operating characteristics curve, logistic regression using triage scores (Revised Trauma Score and Mechanism Glasgow scale and Arterial Pressure score), and Trauma Related Injury Severity Score as a reference standard. The authors also used a reclassification method. Results: The authors evaluated 1, 075 trauma patients (mean age, 39 ± 18 yr, with 90% blunt and 10% penetrating injuries and a mortality of 13%). At admission, blood lactate was elevated in 425 (39%) patients and base deficit was elevated in 725 (67%) patients. Blood lactate was correlated with base deficit ( R 2 = 0.54; P < 0.001). Using logistic regression, blood lactate was a better predictor of death than base deficit when considering its additional predictive value to triage scores and Trauma Related Injury Severity Score. This result was confirmed using a reclassification method but only in the subgroup of normotensive patients (n = 745). Conclusions: Initial blood lactate should be preferred to base deficit as a biologic variable in scoring systems built to assess the initial severity of trauma patients. Abstract : Initial blood lactate should be preferred to base deficit as a biologic variable in scoring systems built to assess the initial severity of trauma patients.